PELAKSANAAN PEMBAYARAN BEA PEROLEHAN HAK TANAH BANGUNAN (BPHTB) DI KOTA PONTIANAK - FREDERIKA SALSABILA PUTRI NIM. A1012181145 (Jurnal Fatwa Hukum, 2023)
Abstrac Taxes have provided the largest revenue for our beloved country. One of the sources of tax received by the state is the Acquisition Duty of Right on Land and Building. The legal basis for Acquisition Duty of Right on Land and Building voting is Law No. 21 of 1997 concerning Acquisition Duty of Right on Land and Building with the issuance of Law No. 20 of 2000 concerning amendments to Law No. 21 of 1997. The object of Acquisition Duty of Right on Land and Building tax is the acquisition of land and/or building rights. In the implementation of Acquisition Duty of Right on Land and Building collection, there are also issues related to Acquisition Duty of Right on Land and Building calculations, the latest procedures in the process of implementing land and building rights acquisition duties. This research was conducted by normative-empirical law research methods. It refers to legal norms. This research is descriptive. The data that used is primary data and secondary data. Data collection methods are data from various reading sources, such as legislation, books, scientific journals, and the internet whose value is relevant to the problems discussed.The results of this research can be concluded that in the implementation of Acquisition Duty of Right on Land and Building collection there are several stages that must be passed, namely the Stage when taxes are owed, the calculation stage of the amount of land and building rights acquisition duties that must be paid and how to calculate it. Keywords: Acquisition Duty of Right on Land and Building. AbstrakPajak telah memberikan penerimaan terbesar bagi negara Indonesia tercinta ini. Salah satu sumber pajak yang diterima oleh negara adalah Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB). Dasar hukum pemungutan BPHTB adalah Undang-undang Nomor 21 Tahun 1997 tentang Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) dengan dikeluarkannya Undang-undang Nomor 20 Tahun 2000 tentang perubahan atas Undang-undang Nomor 21 Tahun 1997. Obyek pajak BPHTB adalah perolehan hak atas tanah dan atau bangunan. Dalam pelaksanaan pemungutan BPHTB juga terdapat masalah yang menyangkut tentang perhitungan BPHTB dan prosedur terbaru dalam proses melaksanakan Bea Perolehan Hak Atas Tanah dan Bangunan.Penelitian ini dilakukan dengan metode Penelitian Hukum Normatif-Empiris. yaitu mengacu pada norma-norma hukum. Penelitian ini bersifat deskriptif. Data yang digunakan adalah data primer dan data sekunder. Metode pengumpulan data adalah data dari berbagai sumber bacaan, seperti perundang-undangan, buku-buku, jurnal ilmiah, dan internet yang nilainya relevan dengan permasalahan yang dibahas.Hasil penelitian ini dapat disimpulkan, dalam pelaksanaan pemungutan BPHTB terdapat beberapa tahapan yang harus dilalui, yaitu Tahap Saat Pajak Terutang, Tahap Perhitungan Besarnya Bea Perolehan Hak Atas Tanah dan Bangunan yang harus dibayar dan cara perhitungannya.Kata Kunci: Bea Perolehan Hak Tanah Bangunan (BPHTB).